Wheat irrigation in a "cerrado" soil of Minas Gerais state, Brazil - de Albuquerque, Paulo Emílio Pereira; Brito, Ricardo Augusto Lopes; de Oliveira, Antônio Carlos (Pesquisa Agropecuaria Brasileira, 1992)
A field experiment of wheat irrigated by sprinkler was set up in a «Cerrado» region, at Sete Lagoas, MG, Brazil. The objective was to obtain the grain productivities by interacting irrigation levels (I) and N levels. The BR-10 cultivar was grow in a dark-red Latossol, in a winter season (June-September). The experimental test used was in strips with five N levels, five irrigation levels and four replications, totalizing 100 plots of 4 x 6 m each. Irrigation was supplied by a line-source system. The best results were obtained with the highest irrigation level (I5 = 700 mm, which is in conformity with 380 mm of consumed water or 92% of total crop evapotranspiration), in which the estimated maximum productivity was about 3.300 kg/ha for a N level of 175 kg/ha. Quadratic curves of estimated productivity and dose of N were plotted for the water levels. In its complete cycle, the wheat received 18 irrigations with four to seven-day intervals.
Keywords: sprinkler irrigation; water x N interaction; productivity of wheat; "Cerrados"; line-source